Investigation of the Relation between High Fructose Corn Syrup Consumption and Stress-Induced Behavioural Changes - Bulmus, Ozgur; Zorlu, Gokhan; Ercan, Zubeyde; Bulmus, Funda Gulcu; Serhatlioglu, Ihsan (Karger, 2018)
[Abstract Not Available]
3rd International Congress of the Turkish-Neuroendocrinology-Society -- JUN 29-JUL 01, 2018 -- Malatya, TURKEY